Sovereign credit ratings, emerging market risk and financial market volatility - Helmut Reisen; Julia von Maltzan (Hamburg Institute of International Economics (HWWA), 1998)
This study has investigated to which extent rating events influence sovereign bond yield spreads and overall financial market volatility. While rating agencies are part and parcel of today's financial markets, the study succeeds in tracing some independent effect that ratings exert on financial market prices. First, our Granger causality test cautions against overestimating the independent longrun impact that sovereign credit ratings exert on the financial-market assessment of sovereign risk, however. The financial market and the two leading rating agencies appear broadly to share the same model in that assessment. As indicated by the explanatory power of the equations that underlie the causality test, dollar bond spreads and a set of default determinants seem to explain somewhat better the level of credit ratings than vice versa. The mutual interaction between sovereign yield spreads and ratings may be characterised by the nature of sovereign risk (requiring assessments on present and future willingness rather than only ability to pay), the information content of sovereign risk ratings (,,contaminating“ rating changes with other publicly-available news) and the industrial organisation of the rating industry (introducing an upward bias in sovereign ratings). Second, contrary to our expectations, our event studies find a highly significant announcement effect – obviously muted by strong market anticipation – when emerging-market sovereign bonds are put on review with negative outlook. The result may surprise, beyond the above considerations, because the rating of these bonds is fairly new to the industry; this lack of experience is reflected by a high degree of split ratings. Negative rating announcements seem also to be effective in the aftermath of rating deteriorations (possibly not fully captured by the length of our observation window), as investors are incited to reorient their portfolios. Positive rating events, by contrast, do not seem to have a significant announcement effect on dollar bond spreads. However, significant effects were found on changes in volatility levels of yield spreads and stock market returns. Third, these findings imply that the sovereign rating industry has the potential to help dampen excessive private capital inflows into the emerging markets with negative rating announcements. Positive announcements, by contrast, do not seem to exert a significant impact on sovereign risk assessments and thus are unlikely to add to the Harberger externality, even though they tend to reduce volatility in both bond and stock markets. For two reasons, even this conclusion must be cautioned however. The econometric analysis of rating decisions seems sensitive to the sample period chosen and the proxy variable for sovereign country risk. And even if rating agencies have the potential to dampen excessive inflows, our analysis does not provide information whether the agencies would provide negative rating announcements in time.
Keywords: 330; Länderrisiko; Aufstrebende Märkte; Ankündigungseffekt; Internationaler Finanzmarkt; Volatilität; Schätzung; Welt